Teaching psychology : a step-by-step guide - Lucas, Sandra Goss, ....-; Bernstein, Douglas A., 1942- (London : Psychology Press / Routledge, 2014)
This volume provides thoroughly updated guidelines for preparing and teaching an entire course in psychology. Based on best principles and effective psychological and pedagogical research, it offers practical suggestions for planning a course, choosing teaching methods, integrating technology appropriately and effectively, developing student evaluation instruments and programs, and ideas for evaluation of your own teaching effectiveness. While research-based, this book was developed to be a basic outline of "what to do" when you teach. It is intended as a self-help guide for relatively inexperienced psychology teachers, whether graduate students or new faculty, but also as a core reading assignment for those who train psychology instructors. Experienced faculty who wish to hone their teaching skills will find the book useful, too.
Keywords: Psychologie ; onderwijs ; didactiek